The Impact of Additional Chromosomal Abnormalities in Response to Imatinib Mesylate Therapy for Chronic Myeloid Leukemia - Otero, Luize (2007)
Imatinib induces a complete cytogenetic response in more than 80% of newly diagnosed patients with chronic myeloid leukemia (CML) in the chronic phase (CP) and in 41% of patients in the first chronic phase after failure of interferon-α treatment. However, some patients do not respond completely. Therefore, according to most studies, drug resistance in CML patients treated with imatinib is correlated with cytogenetic abnormalities acquired during treatment. In this study we analyzed 48 CML patients treated with imatinib mesylate after interferon-_ resistance in order to elucidate the impact of additional chromosomal abnormalities prior to imatinib in response to therapy. Cytogenetic abnormalities in addition to the Philadelphia chromosome (Ph) were detected in 33.3% of patients. Patients with Ph as the sole cytogenetic abnormality prior to imatinib therapy presented a major cytogenetic response and significantly longer median overall survival (p=0.006) than patients with additional chromosomal abnormalities. Therefore, in this group of patients, another choice of treatment should be considered, such as stem cell transplantation or combination regimens as appropriate. The present study indicates the importance of detecting a double Ph chromosome prior to imatinib therapy. Patients showing this abnormality did not respond to imatinib, thus indicating the abnormality's association with resistance. Our study suggests that classical cytogenetic analysis is still an important tool prior to and during follow-up of CML patients treated with imatinib.